n-UV-Converted Enhanced Downshifting Blue Emission through Bi3+ Sensitization in Self-Activated LaNbO4 Phosphors for LEDs and High Broadband Quantum Cutting Efficiency for Solar Cell Applications - Modanwal S.; Roy A.; Rai A.; Uttam K.N.; Singh A.P.; Jit S.; Mishra H.; Rai S.B. (My University, 2025)
This paper reports the downshifting (DS) and quantum cutting (QC) emissions in Bi3+-sensitized self-activated LaNbO4 and LaNbO4/Yb3+ phosphor materials. The Bi3+ and Yb3+ ion-doped/codoped phosphor materials were synthesized at 1473 K by a solid-state reaction method. The structural and optical characterization techniques have been carried out by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), photoluminescence (PL), and lifetime measurements. LaNbO4 gives intense blue emission in the 350-600 nm region, with the maximum in the violet-blue region at 418 nm on ultraviolet (UV) excitation. The PL emission intensity was found to increase on doping of the Bi3+ ion. It is found that at lower concentrations (≤0.08 mol %), Bi3+ behaves as a sensitizer; however, at higher concentrations (>0.5 mol %), it acts as an activator by producing its own emission due to 3P1 → 1S0 transition. The behavior of phosphors from low to high concentrations of Bi3+ has been investigated in detail by lifetime measurements and a suitable energy level diagram. The self-activated broad blue-emitting behavior of doped LaNbO4:10Yb3+, xBi3+ has been used to produce strong QC near-infrared (NIR) emission on UV excitation (262 nm) at 0.08 (i.e., as a sensitizer) and at 2 mol % (as an activator) Bi3+ concentrations. The maximum broadband QC efficiency is found to be 148% in the LaNbO4:0.08 Bi3+, 10Yb3+ phosphor at optimized Bi3+ and Yb3+ concentrations. We also investigated the QC emission at two distinct concentrations (0.08 and 2 mol %, i.e., sensitizer and activator, respectively) with varied Yb3+ concentrations from 0 to 13 mol % and compared with different other QC emitting phosphors. The LaNbO4 host and Bi3+ ions (3P1 level) both transfer energy to Yb3+ ions in two ways, and the two-step intense broadband quantum cutting would result in intense NIR emission. The NIR emission generated by this type of QC process can be used to enhance the efficiency of solar cells. The LaNbO4:Bi3+ phosphor emits intense DS emission with high color purity (88.8%) in the blue region and therefore has been employed to produce an n-UV-converted strong blue source for light-emitting diode (LED) application. © 2025 American Chemical Society.